Occurrence of Salmonella spp. in broiler chicken carcasses and their susceptibility to antimicrobial agents Ocorrência de Salmonella spp. em carcaças de frango e sua suscetibilidade a agentes antimicrobianos - Dalila Angélica Moliterno Duarte (Brazilian Journal of Microbiology, 2009)
The present study was carried out to evaluate the occurrence of Salmonellae in broiler chicken carcasses and to determine the antimicrobial resistance profile of the isolated strains. Twenty-five out of the 260 broiler chicken carcasses samples (9.6%) were positive for Salmonella. S. Enteritidis was the most frequent serovar. Nineteen Salmonella isolates were tested for antimicrobial resistance, and the results indicated that 94.7% were resistant to at least one antimicrobial agent. Resistance to streptomycin (73.7%), nitrofurantoin (52.3%), tetracycline (31.6%), and nalidixic acid (21%) were the prevalent amongst Salmonella strains tested. O presente estudo teve como objetivo verificar a ocorrência de Salmonellae em amostras de carcaças de frango e a suscetibilidade dos isolados a agentes antimicrobianos. Das 260 carcaças analisadas, 25 (9,6%) foram positivas para Salmonella. Salmonella Enteritidis foi o sorovar predominante. Com relação à suscetibilidade a agentes antimicrobianos, 94,7% das cepas de Salmonella testadas, apresentaram resistência a um ou mais agentes antimicrobianos. Os perfís de resistência mais comumente observados entre os isolados foram a resistência à estreptomicina (73,7%), nitrofurantoína (52,3%), tetraciclina (31,6%) e ácido nalidíxico (21%).